2021
DOI: 10.1039/d0cc07721f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning metal–metal interactions for cooperative small molecule activation

Abstract: This Feature Article describes recent advances in the design of multinucleating ligands that support small molecule activation chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 150 publications
0
65
0
Order By: Relevance
“…Remarkable advances in homogeneous catalysis have been achieved with systems comprising late transition metals and PDI ligands. To date, several multinuclear transition-metal complexes supported by macrocyclic ligands bearing two or more PDI moieties have been developed, and they exhibited interesting reactivity differences in catalytic ethylene polymerization compared to analogous mononuclear complexes. However, current uses of bis-PDI-based dinuclear complexes in the catalytic methodology are still in their infancy and further research efforts are warranted. In 2017, Tomson and co-workers reported an attractive work describing the dicobalt­(II) complexes bound by pyridyl diimine-containing macrocyclic ligands with flexible links. Additionally, each cobalt atom was bonded by a PMe 3 ligand, which can further react with the dicobalt-bridging nitrides. Our approach to the development of the dinuclear cobalt molecular catalyst was inspired by the unique catalytic performance of Co 2 (CO) 8 and pioneering work from the Tomson group, and the phosphine ligand-free bis-PDI dicobalt complex was developed since appropriate empty coordination sites are required for catalysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable advances in homogeneous catalysis have been achieved with systems comprising late transition metals and PDI ligands. To date, several multinuclear transition-metal complexes supported by macrocyclic ligands bearing two or more PDI moieties have been developed, and they exhibited interesting reactivity differences in catalytic ethylene polymerization compared to analogous mononuclear complexes. However, current uses of bis-PDI-based dinuclear complexes in the catalytic methodology are still in their infancy and further research efforts are warranted. In 2017, Tomson and co-workers reported an attractive work describing the dicobalt­(II) complexes bound by pyridyl diimine-containing macrocyclic ligands with flexible links. Additionally, each cobalt atom was bonded by a PMe 3 ligand, which can further react with the dicobalt-bridging nitrides. Our approach to the development of the dinuclear cobalt molecular catalyst was inspired by the unique catalytic performance of Co 2 (CO) 8 and pioneering work from the Tomson group, and the phosphine ligand-free bis-PDI dicobalt complex was developed since appropriate empty coordination sites are required for catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, extensive efforts to isolate II and get its crystal structure failed. Computational results showed that a folded PDI ligand conformation of intermediate II ( S = 1, Scheme ) is 1.3 kcal/mol more stable than the parallel ligand conformation (Table S5 in the Supporting Information). And the Co α –Co β distance located at 2.47 Å, implying a plausible metal–metal single bond character with 0.52 Mayer bond order (MBO). The Δ value is a single parameter combined by the values of C im –N im ,C im –C py and C py -N py distances, which is a powerful structural parameter for the determination of the oxidation level of the PDI ligand .…”
Section: Resultsmentioning
confidence: 99%
“…However, many other redox-active motifs are currently known. Recently, Tomson described a series of macrocyclic complexes that feature two (PDI)­M units connected by alkyl tethers . Given our observation that (NDI)­Ni 2 -catalyzed processes can require the reversible formation and cleavage of Ni–Ni bonds, it is interesting to consider the implications of such ligands with added conformational flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…There is no universal classification scheme. Sometimes systems are considered based on the degree of metal-metal interaction, 46,48 the ligand scaffold, 46,48 the polarity or Lewis acidity/basicity of the metals, 16 or the mode of substrate activation. 49 Instead, we have presented examples herein by reaction type and substrate.…”
Section: Metal-metal Cooperativitymentioning
confidence: 99%